Educator Performance in Terms of Certification, Workload, and Educator Well-being - Rr. Maylinda Divarukmi K.; Najwa Rihadatul‘Aisy; Suparmi (Konsultan Jurnal Ilmiah Indonesia, 2024)
Educational performance is very important because it is the spearhead of a country's development to avoid poverty and improve the welfare of its citizens. Good quality education comes from the teaching staff it has. However, problems occur when the country lacks teaching staff. In addition, the demands for certification are a burden and the mismatch in welfare received. This study aims to 1) find out whether the performance of educators can be influenced by certification, 2) find out whether the performance of educators can be influenced by workload, 3) find out whether the performance of educators can be influenced by the welfare of educators. The research method used is a literature review. The process of searching for articles by referring to issues related to educators. From these issues, journal searches use the keywords factors that influence educator performance. The results of the study showed that the performance of educators, both partially and simultaneously, can be influenced by certification, workload, and educator welfare.